The Effects of a Constipation Prevention Program on Incidence and Severity of Constipation in Hospitalized Elderly undergoing Hip Surgery - พวงผกา มั่นหมาย (2018)
Purpose: To examine the effects of constipation prevention program on incidence and severity ofconstipation in hospitalized elderly undergoing hip surgery.